Cerebral Toxoplasmosis with Negative Toxoplasmosis Serology in an HIV-Infected Patient: Case Report - idalene, Malika; Talibi Alaoui, Zahid; El Fargani, Rania; Ait Driss, Wiaam; tassi, noura (International Journal of Innovative Research in Medical Science, 2024)
Cerebral toxoplasmosis is the most common opportunistic infection of the central nervous system during HIV infection in Europe and Africa. The diagnosis is made by a set of clinical, radiological, serological, histological, molecular arguments as well as the response or not to the anti-toxoplasmosis treatment. We report the case of a 52-year-old HIV-infected patient, CD4 count at 11 / mm3, who presented a month before admission with fever and weight loss amounting to 15 kg, headache, memory problems, without signs of deficit or signs of intracranial hypertension. A lumbar puncture (LP) was performed after elimination of contraindications showed isolated hyperproteinorrachia, cerebral computed tomography scan (CT scan) was performed after its availability showed an image of abscess, anti-toxoplasmosis treatment was started, further brain MRI confirmed the abscess image, and toxoplasmosis serology was requested twice and came back negative, PCR for Toxoplasma gondii was requested in cerebrospinal fluid (CSF) and returned positive. The outcome was good clinically and radiologically. A control CT scan performed 3 months after showed almost total disappearance of the lesion. The diagnosis of cerebral toxoplasmosis must be made in HIV- infected patients in front of any neurological manifestations with suggestive radiological images even with negative serology.